Slurry Dewatering Process to Improve Quality of Low Grade Coal - Hartiniati (IPTEK The Journal for Technology and Science, 2025)
The upgrading Kalimantan low rank coal is performed using slurry dewatering process in a stirred batch autoclave (inner volume of 5 liters) equipped with a condenser, a pressure control valve (PCV), and a receiver. The experiment is carried out at 3.5 kg/cm2G nitrogen pressure, 250oC heater temperature and 150 rpm agitator speed. Kerosene and low sulfur waxy residue (LSWR) are used as oil solvents. The fluidity of slurry is studied with the ratio of oil to coal (O/C) at 1.5 to 2 wt/wt and the concentration of LSWR at 0.5 to 2% in oil. The temperature profile during operation is evaluated to investigate the process performance. Moreover, pH, TSS and TDS contents in water product is also analyzed. A centrifuge separator (cap. 200 gram, 1000 rpm) is used to remove oil in coal slurry, and it is found that almost all added oil can be recovered. The study suggests that calorific value of upgraded coal (as received basis) increases sharply from 5,178 kcal/kg to 7342 kcal/kg, following drastic reduction in total moisture, from 25,5% to 4,97%. The contents of ash, volatile matter and elements do not change very much from that of raw coal. This phenomenon shows that no chemical reaction occurs in the process. The wastewater from the process is clean enough thereby a simple wastewater treatment is required in commercial plant. Re-absorption test shows that stable moisture content in coal is achieved at 7.5 wt% for 13 days. The temperature profile suggests that the slurry dewatering process can be applied effectively to Kalimantan low rank coals producing excellent upgraded coal characteristics.